2002
DOI: 10.4049/jimmunol.169.9.4889
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccination Breaks Tolerance for a Neo-Self Antigen in Liver: A Transgenic Murine Model of Autoimmune Hepatitis

Abstract: Understanding the pathogenesis of autoimmune hepatitis requires an animal model in which chronic progressive immune injury develops spontaneously or with minimal manipulations. The new transgenic mouse model proposed in this study is based on the hypothesis that infectious agents have the potential to initiate autoreactivity through molecular mimicry. A transgenic mouse expressing lymphocytic choriomeningitis virus nucleoprotein (NP) in a H-2b background developed liver injury when vaccinated with plasmids exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 51 publications
4
60
0
1
Order By: Relevance
“…Furthermore, work from Bowen et al [84] showed that specific T cells directed against a liver antigen are not properly activated if this antigen is uniquely expressed in the liver. A break of tolerance towards liver antigens could only be observed when the liver antigen was also expressed in the periphery [47,84,85] . In light of these results, both hepatotropic and non-hepatotropic viruses should be considered as potential triggering events leading to the development of an AIH, through release of autoantigens in a pro-inflammatory environment and/or by molecular mimicry between viruses and autoantigens.…”
Section: Modification or Release Of Sequestered Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, work from Bowen et al [84] showed that specific T cells directed against a liver antigen are not properly activated if this antigen is uniquely expressed in the liver. A break of tolerance towards liver antigens could only be observed when the liver antigen was also expressed in the periphery [47,84,85] . In light of these results, both hepatotropic and non-hepatotropic viruses should be considered as potential triggering events leading to the development of an AIH, through release of autoantigens in a pro-inflammatory environment and/or by molecular mimicry between viruses and autoantigens.…”
Section: Modification or Release Of Sequestered Proteinmentioning
confidence: 99%
“…In the TTR-nucleoprotein (NP) transgenic mouse, which expresses the lymphocytic choriomeningitis virus (LCMV) NP under the control of a liver-specific promoter, DNA vaccination with a plasmid coding for the LCMV-NP led to a liver-specific immune response and a progressive destruction of the hepatic parenchyma [85] . In this case, a molecular identity between the self-protein and the injected antigen was the triggering factor for AIH development.…”
Section: Molecular Mimicrymentioning
confidence: 99%
“…An extended strategy to mimic AIH in mice is based on the administration of Con A, which induces a strong and fast activation of hepatic lymphocytes (7,8). More relevant AIH animal models involve either the induction of an immune response against a specific liver Ag or the use of genetically modified animals expressing neoantigens, and in many cases also require the administration of adjuvants or the expression of immunostimulatory cytokines (9)(10)(11)(12). Alternatively, spontaneous hepatitis takes place in transgenic mice expressing IFN-g constitutively in hepatocytes, in programmed cell death 1 (Pd-1)-null animals subjected to neonatal thymectomy, in Tgf-b-deficient mice, and in mice with conditional deletion of the TNFR-associated factor 6 gene in thymic epithelial cells (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Alternatively, DNA-vaccination with plasmids encoding for target antigens, including CYP2D6 19 , is used to induce hepatitis. However, an additional vaccination with plasmids encoding for pro-inflammatory cytokines, such as IL-12, is required 20 . Unfortunately, with a few exceptions 15,20 hepatitis is only transient.…”
Section: Discussionmentioning
confidence: 99%